Physical activity initiated by employer induces improvements in a novel set of biomarkers of inflammation: an 8-week follow-up study - Lunde, Lars-Kristian (Eur J Appl Physiol, 2017)
PURPOSE: We investigated the level of pro- and anti-inflammatory biomarkers before and after 8 weeks of unsupervised physical activity (PA) initiated by employer. METHODS: During autumn 2014, background data, blood samples and self-reported exercise level were collected from 76 men and 41 women in a Norwegian road maintenance company. Monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), leptin, adiponectin, p-selectin and CD40 ligand (CD40L) were analyzed. [Formula: see text] was measured in a subgroup of 50 subjects. RESULTS: With reference point of exercise ≤1 time/week, we found that participants who exercised 2–3 times/week had higher [Formula: see text] values (5.6 mL kg(−1) min(−1); 95% CI [1.3, 9.9]). MCP-1 was lower in those who exercised ≥ 4 times/week (−81.98 pg/ml [−142.9, −21.0]). IL-6 and p-selectin levels were lower in females who exercised ≥4 times/week (−1.04 pg/ml [−2.04, −0.03] and −13.75 ng/ml [−24.03, −3.48]). Leptin was lower in participants who exercised 2–3 times/week (−0.39 µg/ml ln [−0.68, −0.09]) and ≥4 times/week (−0.69 µg/ml ln [−1.10, −0.28]). During follow-up, [Formula: see text] increased (2.9 mL kg(−1) min(−1) [1.5, 4.3]), while p-selectin and CD40L decreased (−2.33 ng/ml [−3.78, −0.87] and 718.14 ng/ml [−1368, −68]). MCP-1 levels decreased among men (−32.70 pg/ml [−51.21, −14.19]). A joint analysis of all biomarkers (inversed adiponectin) showed that those who exercised ≥4 times/week at baseline had lower total levels of biomarkers and that total biomarker levels decreased during follow-up. CONCLUSIONS: Exercising several times a week was associated with less inflammation compared to exercising once a week or less. During the 8-week follow-up, total levels of biomarkers of inflammation improved. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00421-016-3533-5) contains supplementary material, which is available to authorized users.